Muscle Synergy Characteristics of the Leaping Step Punch Motion and Analysis of Performance Level Differences - Kang, Ziye; Zhang, Chenchen; Zhou, Qizhao; Ma , Yunchao (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details